Forest Landscapes and Global Change 2014
DOI: 10.1007/978-1-4939-0953-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Humans as agents of change in forest landscapes

Abstract: Forest systems play a crucial role in biogeochemical cycling and provide a variety of ecosystem services at multiple scales. Considerable progress has been made in understanding the dynamics of tropical and temperate deforestation and land-use and cover change. However, less attention has been dedicated to understanding the social and biophysical conditions under which reforestation occurs. Recent research documents the experiences of many countries that have undergone transitions from a period of high defores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…The results contribute to understand the current state of land use in rural properties in the state of São Paulo as well as the potential effects of size, economic activity and social group on the conservation of native vegetation in the properties. We found that native vegetation cover in rural lands of São Paulo is generally very low, corroborating results in other spatial research scales (CALABONI et al, 2018;FARINACI et al, 2014;PIVELLO, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results contribute to understand the current state of land use in rural properties in the state of São Paulo as well as the potential effects of size, economic activity and social group on the conservation of native vegetation in the properties. We found that native vegetation cover in rural lands of São Paulo is generally very low, corroborating results in other spatial research scales (CALABONI et al, 2018;FARINACI et al, 2014;PIVELLO, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…METZGER; PERES, 2010), being more suitable to ecological restoration (FARINACI et al, 2014). However, large farms are directly related to global commodity markets, which promote deforestation in the tropics (DEFRIES et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Iverson et al (2014) They are also affected by different drivers, such as climate change. Farinaci et al (2014) discuss this in Chapter 4 of this book. Biodiversity, even more than other ecosystem and landscape components, has been affected by forest landscape changes of many different types and origins, and potentially in irreversible ways in some parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we lack a full understanding of the complex feedback loops among the drivers of change and their effects. Farinaci et al (2014) discuss this in Chapter 4 of this book. Furthermore, the lack of knowledge of carbon distribution, temporal changes in this distribution, and the underlying regulatory mechanisms for many ecosystem components limits our understanding of carbon cycles.…”
Section: How Much Do We Really Know?mentioning
confidence: 99%